Risk Factors for Underdiagnosis of Diabetes Based on the Korean National Health and Nutrition Examination Survey 2013-2015. (July 2019) - Min, Deulle; Cho, Eunhee
We included 11 298 subjects aged 30 years or older without diagnosis of diabetes by doctors who had undergone A1C screening. The diagnostic criterion for diabetes was A1C ≥6.5% (48 µmol/mol). This cross-sectional study was performed by reflecting weight of the sample in Korean National Health and Nutrition Examination Survey to represent South Korea. Risk factors were age (odds ratio [OR] = 1.06, 95% confidence interval [CI] = 1.04-1.08), Medicaid beneficiary (OR = 2.77, 95% CI = 1.25-6.14), presence of family history of diabetes (OR = 1.97, 95% CI = 1.36-2.84), serum triglyceride level (OR = 1.01, 95% CI = 1.01-1.03), serum high-density lipoprotein level (OR = 0.96, 95% CI = 0.95-0.98), currently smoking (OR = 1.85, 95% CI = 1.20-2.85), and the presence of regular checkup (OR = 1.41, 95% CI = 1.01-2.00). To prevent diabetes with a healthy life, it is necessary to establish a diabetes prevention program for vulnerable people and implement health-related policies such as smoking cessation and regular checkups.